CONTEMPORARY PERCEPTIONS ABOUT CHRISTIANITY: EXPLORING CHINESE CHRISTIANS’ TESTIMONIES 2003-2009 - Chung, Yu Ling (Journal of Al-Tamaddun, 2011)
For Chinese, Christianity used to be viewed as a foreign religion forced into China by the hegemony of the West. Christianity also tends to remind them of a period of humiliating history since the late nineteenth century. However, Christianity for contemporary Chinese Christians in the twenty-first century, especially those from Taiwan, has become a channel to approach Western cultures and histories. Some Chinese Christians first have access to Christianity out of the motive of learning English. In other words, their perceptions of Christianity may have been changed. Writing testimonies has become a ritual for about-to-be-baptized Chinese Christians as a verification of their belief. The big transformations happened in their lives before and after they accepted Christianity are often emphasized in their testimonies. Setbacks such as illness, failures or accidents diverging them from original life tracks, are usually the turning point for their attitude change toward Christianity, from objection and resistance to acceptance and endorsement. The truth they claim is based on the Bible and can obtain by praying to and submitting themselves to Jesus Christ. Some of them also mention the differences between Chinese traditional religions and Christianity and difficulties for Chinese people to accept Christianity. This paper uses a Chinese Christian monthly magazine as corpus to analyze the testimonies within since 2003, offered by Christians from contemporary Chinese communities. Typical testimonies are chosen to probe the adaptive strategies Chinese Christians use while confronting with Christianity, what Christianity and Christians mean to them before and after their conversions, and the narrative devices they use in writing testimonies. Some of the testimonies are in written form, but some are first delivered orally then rewritten and edited by specific writers. The subtitles in these testimonies are added by editors who seemingly follow the norm of introduction (personal background), encountering with Christianity, life transforming and renewing, and concluding with the importance of biblical teachings. The circumstances of moving between spoken and written testimonies are investigated by interviewing an editor of the magazine.